2020
DOI: 10.3762/bjnano.11.76
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electrostatic tip–sample interactions by time-domain Kelvin probe force microscopy

Abstract: Kelvin probe force microscopy is a scanning probe technique used to quantify the local electrostatic potential of a surface. In common implementations, the bias voltage between the tip and the sample is modulated. The resulting electrostatic force or force gradient is detected via lock-in techniques and canceled by adjusting the dc component of the tip–sample bias. This allows for an electrostatic characterization and simultaneously minimizes the electrostatic influence onto the topography measurement. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Its implementation requires only using a few basic analog circuits to synchronously maintain the compensation bias and switch off the modulation voltage; it should also be easy to develop numeric counterparts directly integrated in last generation digital scanning probe microscope controllers. Like in the case of graphene [15], we have shown that conventional nc-AFM/KPFM measurements cannot assess correctly the stacking height of 2D TMD deposited on silicon-oxide substrates. This further highlights just how the variations of the tip-sample capacitance can affect the topographic measurement, despite the CPD compensation by the KPFM controller.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Its implementation requires only using a few basic analog circuits to synchronously maintain the compensation bias and switch off the modulation voltage; it should also be easy to develop numeric counterparts directly integrated in last generation digital scanning probe microscope controllers. Like in the case of graphene [15], we have shown that conventional nc-AFM/KPFM measurements cannot assess correctly the stacking height of 2D TMD deposited on silicon-oxide substrates. This further highlights just how the variations of the tip-sample capacitance can affect the topographic measurement, despite the CPD compensation by the KPFM controller.…”
Section: Discussionmentioning
confidence: 77%
“…From what precedes, it is also clear that the question of electrostatic-related artefacts in dynamic AFM has long been overlooked by the AFM community. Only very recently, a few teams have rightly pointed out that electrostatic forces can misleadingly influence the stacking height measurement of 2D materials by AFM [14,15]. To address this problem, one may be tempted to apply an active KPFM loop to compensate the tip-surface potential difference.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the following experiments, open loop time-domain KPFM 44 is applied. In contrast to the FM-KPFM 19 configuration in Figure 1b…”
mentioning
confidence: 99%
“…For the following experiments, open loop time-domain KPFM 44 is applied. In contrast to the FM-KPFM 19 configuration in Figure 1 b–d,f–h, where a phase-locked loop controls the cantilever phase response, the time-domain KPFM technique directly records the phase-time series.…”
mentioning
confidence: 99%